Photoactive Nanocarriers for Controlled Delivery. (28th August 2019) - Xiong, Qirong; Lim, Yun; Li, Di; Pu, Kanyi; Liang, Li; Duan, Hongwei
Abstract: Photoactive nanocarriers have emerged as robust and minimally invasive systems for the on‐demand delivery of active payloads. The easy manipulation offered by light irradiation as an external stimulus allows precise spatiotemporal control of payload release based on the time, intensity, location, and wavelength of light exposure. Compared to conventional passive delivery systems, photoactive nanocarriers offer the possibility of tailoring the release kinetics of the encapsulated active molecules, which is of considerable clinical relevance for targeted delivery to desired sites of interest. In this progress report, the recent advances in the design and fabrication of photoactive nanoplatforms based on three main modes of mechanisms: photochemical reactions, the photothermal effect, and photosensitization mechanism mediated by reactive oxygen species are highlighted. The combination of these mechanisms provides additional flexibility for the effective delivery of therapeutics and improved synergistic therapeutic effects. Finally, challenges in future perspectives on the development of photoactive nanomaterials and their medical translation are discussed. Abstract : Photoactive nanocarriers are robust and minimally invasive systems for on‐demand delivery of active cargos. Photocontrolled delivery offers precise spatiotemporal control by location, time, intensity, and duration of light exposure. Light‐triggered delivery systems offer versatile modes of payload release: photochemical reactions, photothermal effects, and photosensitization.